Suppression of circadian clock protein cryptochrome 2 promotes osteoarthritis. Issue 7 (July 2020) - Bekki, H.; Duffy, T.; Okubo, N.; Olmer, M.; Alvarez-Garcia, O.; Lamia, K.; Kay, S.; Lotz, M.
Summary: Objectives: Abnormal chondrocyte gene expression promotes osteoarthritis (OA) pathogenesis. A previous RNA-sequencing study revealed that circadian rhythm pathway and expression of core clock gene cryptochrome 2 ( CRY2 ) are dysregulated in human OA cartilage. Here we determined expression patterns and function CRY1 and CRY2 . Methods: CRY mRNA and protein expression was analyzed in normal and OA human and mouse cartilage. Mice with deletion of Cry1 or Cry2 were analyzed for severity of experimental OA and to determine genes and pathways that are regulated by Cry . Results: In human OA cartilage, CRY2 but not CRY1 staining and mRNA expression was significantly decreased. Cry2 was also suppressed in mice with aging-related OA. Cry2 knock out (KO) but not Cry1 KO mice with experimental OA showed significantly increased severity of histopathological changes in cartilage, subchondral bone and synovium. In OA chondrocytes, the levels of CRY1 and CRY2 and the amplitude of circadian fluctuation were significantly lower. RNA-seq on knee articular cartilage of wild-type and Cry2 KO mice identified 53 differentially expressed genes, including known Cry2 target circadian genes Nr1d1, Nr1d2, Dbp and Tef . Pathway analysis that circadian rhythm and extracellular matrix remodeling were dysregulated in Cry2 KO mice. Conclusions: These results show an active role of the circadian clock in general, and of CRY2 in particular, in maintaining extracellular matrix (ECM) homeostasis in cartilage. This cell autonomous network of circadian rhythm genes is disrupted in OA chondrocytes. Targeting CRY2 has potential to correct abnormal gene expression patterns and reduce the severity of OA.